2021
DOI: 10.1371/journal.ppat.1009724
|View full text |Cite
|
Sign up to set email alerts
|

A non-neutralizing antibody broadly protects against influenza virus infection by engaging effector cells

Abstract: Hemagglutinin (HA) is the immunodominant protein of the influenza virus. We previously showed that mice injected with a monoglycosylated influenza A HA (HAmg) produced cross-strain-reactive antibodies and were better protected than mice injected with a fully glycosylated HA (HAfg) during lethal dose challenge. We employed a single B-cell screening platform to isolate the cross-protective monoclonal antibody (mAb) 651 from mice immunized with the HAmg of A/Brisbane/59/2007 (H1N1) influenza virus (Bris/07). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 54 publications
(75 reference statements)
1
13
0
1
Order By: Relevance
“…A large portion of specific IgG antibodies detected in 293T cell-expressed H5+N6 protein antisera may be the non-neutralizing antibody. Although non-neutralizing antibody is not able to prevent viral infection, it may still contribute to antiviral protection through other antibody-mediated effects, such as antibody-dependent cellular cytotoxicity (ADCC), antibody-dependent cellular phagocytosis (ADCP) or antibody-mediated complement-dependent cytotoxicity (CDC) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large portion of specific IgG antibodies detected in 293T cell-expressed H5+N6 protein antisera may be the non-neutralizing antibody. Although non-neutralizing antibody is not able to prevent viral infection, it may still contribute to antiviral protection through other antibody-mediated effects, such as antibody-dependent cellular cytotoxicity (ADCC), antibody-dependent cellular phagocytosis (ADCP) or antibody-mediated complement-dependent cytotoxicity (CDC) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the neutralization antibodies, the nonneutralizing antibodies against the influenza virus also have demonstrated that they play a key role in protection according to their Fc-mediated responses (102,103). Indeed, a large number of non-neutralizing antibodies can broadly cross-react with coronaviruses (104).…”
Section: Omicron Variant: Good News Exists Beyond "Neutralization"mentioning
confidence: 99%
“…In addition to binding via the antigen-binding fragment (Fab) region of the antibodies, the crystallizable fragment (Fc) region of antibodies plays a key role in recruitment of complement and activation of cellular effector mechanisms, most notably via ADCP by FcγR2a [ 34 ] and ADCC by FcγR3a [ 35 37 ]. Increased interactions of WPV-induced antigen-specific antibodies with these receptors suggests that apart from direct inhibition of viral entry in the event of infection, these antibodies also have the potential to engage Fc receptors on effector cells to facilitate cytolysis of virally-infected cells [ 38 ] and phagocytosis of opsonized material by cells expressing these receptors [ 34 ], thus can contribute to overall protection against infection and disease severity [ 39 ]. The engineering of low affinity FcγR ectodomains as a linked dimer confers avid binding only by pairs of IgG that occupy closely spaced (“near-neighbor”) epitopes [ 40 ].…”
Section: Discussionmentioning
confidence: 99%